Desain dan Simulasi Ultra Step-Up Converter pada Mobil Listrik dengan Kontrol Fuzzy Logic - Rifqi Dary Suryanto; Era Purwanto; Syechu Dwitya Nugraha (Politeknik Negeri Batam, 2021)
The battery is an important part used to drive motors and instruments in electric cars, but the number of batteries used needs to be considered to adjust the required working voltage. If a three-phase induction motor is used to drive an electric car, a battery voltage of 326 Vdc is required which is then supplied to a three-phase inverter to 230 Vac which will then be used as a supply to a 3-phase induction motor. So that to decrease the number of batteries to be used in this study, a voltage booster system, namely the Ultra Step-Up Converter will be designed which functions to increase the working voltage of the battery which was originally 48Vdc until the output voltage of 326 Vdc is obtained which can be loaded up to 1.2 kW. This converter will be added with fuzzy logic control to control the output voltage so that it remains constant at 326 Vdc even though the voltage on the battery varies.